Measuring Mindreading: A Review of Behavioral Approaches to Testing Cognitive and Affective Mental State Attribution in Neurologically Typical Adults - Turner, Rose; Felisberti, Fatima M. (Frontiers in Psychology, 2017)
“Mindreading” refers to the ability to attribute mental states, including thoughts, intentions and emotions, to oneself and others, and is essential for navigating the social world. Empirical mindreading research has predominantly featured children, groups with autism spectrum disorder and clinical samples, and many standard tasks suffer ceiling effects with neurologically typical (NT) adults. We first outline a case for studying mindreading in NT adults and proceed to review tests of emotion perception, cognitive and affective mentalizing, and multidimensional tasks combining these facets. We focus on selected examples of core experimental paradigms including emotion recognition tests, social vignettes, narrative fiction (prose and film) and participative interaction (in real and virtual worlds), highlighting challenges for studies with NT adult cohorts. We conclude that naturalistic, multidimensional approaches may be productively applied alongside traditional tasks to facilitate a more nuanced picture of mindreading in adulthood, and to ensure construct validity whilst remaining sensitive to variation at the upper echelons of the ability.